The Effect of Carbon Emissions Disclosure, Earnings Management, Information Asymmetry, and Leverage on the Cost of Equity - Oktaviyanti, Devi; Setijaningsih, Herlin Tundjung; Kasenda, Faris (Institut Bisnis dan Informatika Kesatuan, 2025)
The cost of equity is a key factor in corporate financing, particularly in Indonesia’s energy sector, where environmental and financial transparency face challenges due to market inefficiencies and regulatory pressures. The purpose of this study is to investigate how the cost of equity is impacted by disclosure of carbon emissions, earnings management, information asymmetry, leverage, profitability, and firm size. The study employs a quantitative methodology, using panel data regression with the Fixed Effect Model in Stata 19.5, to evaluate 111 observations from 37 energy sector companies listed on the Indonesia Stock Exchange between 2021 and 2023. The results demonstrate that profitability, as determined by return on assets, and leverage, as determined by the debt-to-asset ratio, have a major impact on the cost of equity. At the same time, carbon emission disclosure, earnings management, information asymmetry, and company size have insignificant effects. These results, with profitability and company size as control variables, suggest that financial structure and performance strongly shape investor risk perceptions. The study concludes that energy companies should optimize debt and profitability to reduce financing costs and improve environmental disclosure quality to meet investor expectations, contributing to sustainable financing strategies in Indonesia’s energy sector.